The role of food security in maintaining community security during disaster situations in Indonesia: A literature review - Gita Novia Sahara; Kusuma Kusuma; Deffi Ayu Puspito Sari (Priviet Social Sciences Journal, 2026)
Indonesia is among the countries with the highest levels of disaster risk in the world, making disaster risk management a crucial aspect of safeguarding community welfare and security. In addition to causing loss of life and damage to infrastructure, disasters frequently disrupt food systems, affecting food availability, access, utilization, and stability. Such disruptions have the potential to increase food insecurity, social vulnerability, and uncertainty in meeting the basic needs of affected communities. This study aims to analyze the role of food security in maintaining community security during disaster situations in Indonesia using a literature review approach. The study adopts a Systematic Literature Review (SLR) approach to examine relevant literature published between 2020 and 2025, including scientific articles, reports from international organizations, government documents, and regulations related to disaster management and food security. The findings indicate that food security plays a strategic role in supporting community security by ensuring the fulfillment of basic needs, reducing the risk of hunger, decreasing social vulnerability, and fostering a sense of security during times of crisis. Food reserves, resilient food systems, and effective logistics management are critical factors in maintaining access to food when disasters disrupt food production and distribution. The study also highlights the importance of strengthening local food production, community food reserves, food diversification, and disaster logistics systems as integral components of disaster risk reduction efforts. Therefore, food security should be integrated into disaster management policies and community resilience-building strategies to enhance the capacity of communities to withstand and recover from disaster impacts. Accordingly, food security should be viewed not only as a development issue but also as a strategic instrument for maintaining community security in disaster-prone areas.